The Hunger Games - Collins, Suzanne (New York : Scholastic Press, 2008)
In a future North America, where the rulers of Panem maintain control through an annual televised survival competition pitting young people from each of the twelve districts against one another, sixteen-year-old Katniss's skills are put to the test when she voluntarily takes her younger sister's place.
The tributes -- The games -- The victor.
Accelerated Reader/Renaissance Learning
Notable Social Studies Trade Books for Young People, 2009
Keywords: Survival -- Juvenile fiction; Television programs -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Contests -- Juvenile fiction; Survival -- Fiction; Television programs -- Fiction; Interpersonal relations -- Fiction; Contests -- Fiction; Science fiction; Young adult fiction